Manggopoh dalam Bingkai: Weaving the History of Siti Manggopoh Into the Choreography of a Dance Work - Quinta Sari; Venny Rosalina (Gondang: Jurnal Seni dan Budaya, 2023)
The figure of Siti Manggopoh is an inspirational Minangkabau woman who fought for human rights. The dance work "Manggopoh Dalam Bingkai" showcases and symbolizes her unwavering spirit as she led a war against the Dutch. It reflects the traditional martial art of "silek" as the dancers' fundamental movement. This dance work carefully incorporates local idioms with distinct Minangkabau nuances, including the setting, music, costumes, dialogue, and etiquette. Its main objective is to nurture creativity in the creation of dance art, an aspect that has been studied throughout the course of education."Manggopoh Dalam Bingkai" sets a benchmark for choreographers aspiring to transform historical events into dance works with compelling storylines. Drawing inspiration from the phenomenal figure of Siti Manggopoh, this production aims to preserve and carry forward the precious local wisdom from the land of Minang.Through this dance work, we revitalize the spirit of resilient and courageous Minangkabau women. It serves as a powerful reminder of the values of bravery, tenacity, and an unyielding spirit in defending their homeland from oppression. With its captivating movements and expressions, "Manggopoh Dalam Bingkai" aims to inspire present and future generations to cherish and continue the struggle and cultural heritage of great significance.